Profile of Mathematics and English Proficiency as well as Mathematical Literacy of Pre-Service Mathematics Teachers in the Era of Technology-Based Education - Teresa Panjaitan, Agnes (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the profile of pre-service mathematics teachers regarding their mathematical proficiency, English language competence, and mathematical literacy in the context of technology-driven education. As digital learning resources increasingly demand the integration of content knowledge, language skills, and higher-order thinking, this study investigates the extent to which these future educators are prepared. Using a mixed-methods approach involving diagnostic tests, literacy tasks, and interviews, the results show that students exhibit moderate mastery in mathematics and basic English but struggle with applying concepts in real-life problem-solving situations—an indicator of low mathematical literacy. The study calls for curriculum redesign that bridges content, language, and technology to better equip future teachers.